THE IMPORTANCE OF MARKETING SERVICES IN THE DEVELOPMENT OF SMALL BUSINESS (Academicia Globe: Inderscience Research, 2022)
The article deals with the implementation of the laws of a market economy, consumer demand in the market, the use of marketing services by small businesses to meet consumer demand, marketing services to study the market and develop recommendations for manufacturers, the organization of marketing services in small businesses. , ministries, corporations, corporations and joint-stock companies. In marketing, the work of departments in cooperation with small businesses is widely covered.